Association of autoimmune diseases with the occurrence of osteoarthritis: a gene expression and Mendelian randomization study - Dan, Jing; Lu, Huai Min; Zhou, Xun; Wang, Hong Yuan; Wang, Jia Hao (Frontiers in Medicine, 2024)
Background Observational studies have indicated a potential association between autoimmune diseases and the occurrence of Osteoarthritis (OA), with an increased risk of mortality among affected patients. However, whether a causal relationship exists between the two remains unknown. Methods In the Mendelian randomization (MR) study, we accessed exposure Genome-wide association study (GWAS) data from both the MRC Integrative Epidemiology Unit (MRC-IEU) and the FinnGen consortium. GWAS data for OA were obtained from MRC-IEU. We employed univariable, multivariable, and reverse MR analyses to explore potential associations between autoimmune disorders and OA. Additionally, a two-step mediation MR analysis was performed to investigate indirect factors possibly influencing the relationship between autoimmune disorders and OA. Afterward, we conducted an observational analysis to further explore the relationship between autoimmune disease and occurrence as well as of OA using a real-world database (the MIMIC-IV database). Based on public gene expression sequencing data, we further explored the potential shared pathogenesis between autoimmune diseases and OA. Results In our univariable MR study, we identified five autoimmune diseases that are associated with OA. These include Celiac disease (OR = 1.061, 95% CI = 1.018–1.105, p = 0.005), Crohn’s disease (OR = 1.235, 95% CI = 1.149–1.327, p = 9.44E-09), Ankylosing spondylitis (OR = 2.63, 95% CI = 1.21–5.717, p = 0.015), RA (OR = 1.082, 95% CI = 1.034–1.133, p = 0.001), and Ulcerative colitis (OR = 1.175, 95% CI = 1.068–1.294, p = 0.001). In the mediation effect analysis, it was found that there is no correlation between cytokines and autoimmune diseases and OA. Based on transcriptome data analysis, it was found that metabolism-related pathways play a key role in the co-morbidity of autoimmune diseases and OA. Conclusion Our findings revealed that genes associated with Celiac disease, Crohn’s disease, Ankylosing spondylitis, RA, and Ulcerative colitis were independently linked to the development of OA. Furthermore, we conducted an analysis of potential pathogenic genes between these diseases and OA, offering a novel approach for the simultaneous treatment of multiple conditions.